Evaluation of the Screening Performance of Ultrasonographic Abdominal Circumference and Estimated Fetal Weight in Predicting Small for Gestational Age Newborns - Yusuf Dal; Fatih Akkus; Sebnem Karagun; Ahmet Zeki Nessar; Sefanur Gamze Karaca; Hakan Aytan; Ayhan Coskun (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: We aimed to evaluate the screening performance of estimated fetal weight (EFW) and abdominal circumference (AC) measurements in predicting newborns with birth weight (BW) less than the 10th percentile for birth age (BW <10p).